The Role of Social Capital in Building Knowledge Sharing and Innovative Work Behavior in Holding Company - Dhyah Harjanti; Angelina Desiana Halim (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
To compete in a dynamic environment, companies must continuously innovate. Therefore, companies need to encourage their employees to have innovative behavior. This study examined the effect of structural, cognitive, and relational social capital on innovative work behavior, using knowledge sharing as mediating variable. This study uses quantitative methods, by surveying 328 employees of holding companies. The data is processed using Partial Least Square. The results point out a positive and significant effect of cognitive and relational social capital on knowledge sharing and knowledge sharing on innovative work behavior.